Quantification of b-Carotene from Diplocyclos palmatus Jeff. Fruits Rind by Using High Performance Thin Layer Chromatography - Patil, Avinash; A. Patil, Darshana; Sharma, Abhishek; Chandra, Naresh (Asian Journal of Chemistry, 2010)
A simple TLC method has been developed for the quantification of b-carotene from fruit rind of Diplocyclos palmatus Jeff., using HPTLC plate pre-coated with silica gel 60 F254. The method was developed in petroleum ether (8 mL) and validated in terms of precision, repeatability and accuracy. The linearity range was found to be 6-60 μg mL-1 with correlation coefficients of 0.999, which is indicative of good linear dependence of peak area on concentration. The method permits reliable quantification and showed good resolution and separation from other constituents of extract. Accuracy of the method was checked by conducting recovery studies at three different levels and the average percentage recoveries were found to be 99.41 ± 0.32 %. The amount of b- carotene in fruit rind of Diplocyclos palmatus Jeff. was found to be 0.0065 ± 0.0003 mg g-1. The proposed method was found to be simple, precise, specific, sensitive and accurate. It can be used for routine quality control of herbal material containing b-carotene.